Analisis Kebutuhan Pengembangan Organisasi bagi Sekolah di MTsN Padang Panjang - Siti Nurul Salma (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to analyze the needs for organizational development at MTsN Padang Panjang in order to improve the effectiveness and quality of educational services. In this context, organizational development includes aspects of management, organizational structure, human resources and work culture that support educational goals. The research method used is descriptive qualitative with a case study approach. Data was collected through observation, interviews and documentation. The research results show that MTsN Padang Panjang requires improvement in several aspects, such as training and developing teacher competency, optimizing the role of school management, as well as improving facilities and infrastructure. These findings indicate the importance of planned and sustainable organizational development programs to support the achievement of the school's vision and mission. It is hoped that the recommendations provided will help schools in developing development strategies that suit the needs and challenges they face.